New species of Planchonella (Sapotaceae): one from Borneo and three from New Guinea - Ulf Swenson; Jennifer Kearey; Kent Do; Timothy M. A. Utteridge (Kew Bulletin, 2026)
Summary Planchonella is the largest genus in subfamily Chrysophylloideae (Sapotaceae) and includes 97 described species distributed from the Seychelles to Hawaii with the greatest species diversity in Australia, New Caledonia and New Guinea. There are approximately an additional ten taxa that do not easily conform with known species limits, and/or have been identified by molecular methods as new to science. We describe here four new species, P. cerebrifructa Swenson from Borneo and P. hispida Swenson, P. surculiflora Swenson and P. takeuchii Swenson from New Guinea, all with distinctive autapomorphic characters. Planchonella cerebrifructa is readily distinguished by its velvety, wrinkled young fruit, very similar to the complex, folded appearance of a brain’s surface. Planchonella hispida has hispid indumentum of long, Y-shaped trichomes, in decreasing density along the midrib and on the secondary, tertiary and quaternary venation. Planchonella surculiflora sets inflorescences on lateral shoots, often with one or two leaves borne between the villose flowers. Finally, Planchonella takeuchii , although the flowers are unknown, can be recognised by its characteristic glabrous foliage of broadly elliptic leaves with a tapering apex, short petioles (± 5 mm long) and tertiary leaf venation perpendicular to the primary and secondary veins. Now, with the description of these four species, the genus Planchonella includes 101 described species.

A new endemic species, Planchonella foveata (Sapotaceae), with an updated identification key to the genus in Fiji - Kent Do; Ulf Swenson (Kew Bulletin, 2025)
Summary Planchonella is a large, monophyletic genus in Sapotaceae, containing around 110 tropical shrub and tree species. A new endemic species, P. foveata K.Do & Swenson is described and illustrated from Fiji, accompanied by an identification key to the genus in the archipelago. It grows mainly in lowland habitats and is phylogenetically more closely related to Micronesian and Malukan taxa than to any other species in Fiji. Planchonella foveata is characterised by the presence of many fovea or minute pit-like structures on the abaxial leaf surface, a trait which it shares with P. vitiensis, but which is absent from other species in the archipelago. However, P. foveata is easily recognised by its longer corolla (2.3 – 3.0 mm) vs (1 – 2 mm) in P. vitiensis , its leaves being scattered along the branches, a hairy tuft on the outer sepals and greenish flowers (vs sepals without a hairy tuft and with yellowish flowers). The conservation status of P. foveata is assessed as data deficient (DD) due to the absence of up-to-date knowledge of present vegetation disturbance and its distribution. With our addition, ten species of Planchonella are now recognised in Fiji, all identifiable with the new key presented here.